2014
DOI: 10.1007/s10876-014-0746-9
|View full text |Cite
|
Sign up to set email alerts
|

Electrochemical Detection of H2O2 Based on Fe3O4 Nanoparticles with Graphene Oxide and Polyamidoamine Dendrimer

Abstract: Herein we described a new electrochemical strategy for the detection of hydrogen peroxide employing Fe 3 O 4 magnetic nanoparticles and polyamidoamine dendrimer (PAMAM). Both of them were modified on the surface of gold electrode as the work electrode. The detection of H 2 O 2 was studied by the method of Amperometric i-t Curve. Under the optimized experimental conditions, H 2 O 2 could be detected in a linear calibration range of 2.0 9 10 -5 -1.0 9 10 -3 M with a correlation coefficient of 0.9950 (n = 10), th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(9 citation statements)
references
References 22 publications
0
9
0
Order By: Relevance
“…Under the same conditions, the GC/rGO‐Fe 3 O 4 ‐Chit/ss‐DNA‐CB electrode shows a remarkably higher apmerometric response to H 2 O 2 at all concentrations compared to the GC/rGO‐Fe 3 O 4 ‐Chit/ss‐DNA and GC/rGO‐CB electrodes, representing a very good electrocatalytic activity of the GC/rGO‐Fe 3 O 4 ‐Chit/ss‐DNA‐CB electrode and obvious synergetic effect of CB and Fe 3 O 4 towards the electroreduction of H 2 O 2 . In previous works electrocatalytic effect of Fe 3 O 4 nanoparticles for determination of hydrogen peroxide and catalytic activity of CB have been reviewed. In the present work, we showed that synergetic effect of Fe 3 O 4 and CB for electrocatalytic reduction of H 2 O 2 whould result in a significantly lower detection limit and higher sensitivity.…”
Section: Resultsmentioning
confidence: 99%
“…Under the same conditions, the GC/rGO‐Fe 3 O 4 ‐Chit/ss‐DNA‐CB electrode shows a remarkably higher apmerometric response to H 2 O 2 at all concentrations compared to the GC/rGO‐Fe 3 O 4 ‐Chit/ss‐DNA and GC/rGO‐CB electrodes, representing a very good electrocatalytic activity of the GC/rGO‐Fe 3 O 4 ‐Chit/ss‐DNA‐CB electrode and obvious synergetic effect of CB and Fe 3 O 4 towards the electroreduction of H 2 O 2 . In previous works electrocatalytic effect of Fe 3 O 4 nanoparticles for determination of hydrogen peroxide and catalytic activity of CB have been reviewed. In the present work, we showed that synergetic effect of Fe 3 O 4 and CB for electrocatalytic reduction of H 2 O 2 whould result in a significantly lower detection limit and higher sensitivity.…”
Section: Resultsmentioning
confidence: 99%
“…Those phenomena reflected that more metal oxide products remained on the wear surfaces in the high concentration of H 2 O 2 solutions. The metal oxide products prevented the fresh metal contacting the H 2 O 2 solution, and reduced the further oxidation reaction 26 . Therefore, the CCD in the 70% H 2 O 2 solution decreased sharply as the test time increased and was lower than those in the 30% and 50% H 2 O 2 solutions when the test time exceeded 40 min as shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…This may be because hydrazine can reduce the carbonyl and carboxyl functional groups only. The shift of G-peak from 1601 to 1608 cm −1 is attributed to the decrease in the layer of GO particle or the exfoliation of particles, which depends on the degree of oxidation of graphite and more GO sheet can be formed [29]. The 2D-peak was observed at 2881 cm −1 and the band-shift and its shapes are correlated with the number of rGO layers.…”
Section: Characterization Of Precursorsmentioning
confidence: 95%
“…The residual and vacancies become the main defects of rGO, once these groups are removed. The G-peak is the main spectral feature of rGO-like material derived from the in-plane motion of the carbon atom [29].…”
Section: Characterization Of Precursorsmentioning
confidence: 99%